KONSEP MAHAR (ṢIDĀQ) DALAM HUKUM PERKAWINAN ISLAM: ANALISIS FIKIH TERHADAP KETENTUAN DAN AKIBAT HUKUMNYA - Isman Nuddin Ritonga; Muhammad Amar Adly (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Mahr (ṣidāq) is an essential element in Islamic marriage law and constitutes a mandatory obligation for the prospective husband. Beyond its symbolic function, mahr carries significant legal implications concerning the rights and obligations of spouses. This article aims to analyze the concept of mahr from a contemporary fiqh perspective by examining its normative foundations, legal requirements, and juridical consequences within Islamic marriage. This study employs a library research method with a normative-juridical approach, focusing on contemporary Islamic legal scholarship published within the last five years. The findings reveal that mahr is an exclusive right of the wife that must be fulfilled by the husband, regardless of whether it is explicitly stated in the marriage contract. Furthermore, mahr has ongoing legal consequences, particularly in cases of divorce, annulment, and the protection of women's rights. Therefore, a comprehensive fiqh-based understanding of mahr is crucial for ensuring substantive justice in modern Islamic marriage law.